Réponses

  • Omnes
  • Modérateur confirmé
2014-03-27T19:22:04+01:00
Salut,

1/a.

f(x) = 0
(x-4)(x-3) = 0
Soit x-4 = 0 ou x-3 = 0
x - 4 = 0        ou x - 3 = 0
x = 4              ou x = 3

g(x) = 0
0.5x(x-4)= 0
Soit 0.5x = 0 ou x-4  = 0
0.5x = 0        ou x -4 = 0
x = 0             ou x = 4

2/

a. Tu traces
b. Les deux points sont les points d'abscisse 4 et 6.

3/

f(x) = g(x)
(x-4)(x-3) = 0.5x(x-4)
(x-4)(x-3) - 0.5x(x-4) = 0
(x-4)[x-3 - 0.5x] = 0
(x-4)(0.5x - 3) = 0
x - 4 = 0
x = 4

0.5x -3 = 0
0.5x = 3
x = 6

S = {4;6}

Bonne soirée !